VISUAL DIDACTIC REGULATORS OF LOGICAL-SEMANTIC TYPE - V. E. Shteinberg; N. N. Manko (Образование и наука)
Introduction. There is a growing recognition that information flows are developing at a geometric rate. These information flows require to be quickly and qualitatively processed for further sustainable development of scientific and production spheres. Thus, the education system requires the search of adequate means of consumption and broadcast of information, knowledge, data, actual material, etc., corresponding to psychological features of perception and thought processes. Visualization as the most convenient and compact form of different submission of data is becoming a key civilization trend of the information age.The aim of the publication is to justify the necessity of designing and applying new didactic means – visual didactic regulators of the logical-semantic type aimed at improving of teaching technologies.Methodology and research methods. The research methodology includes the concept of logical and semantic modeling of knowledge presented in natural language, and the concept of orienting bases of actions in teaching. The method of the present research is graphic visualization of logical and semantic modeling of knowledge.Results. The definition of the concept “visual didactic regulators of the logical-semantic type” is formulated; its characteristics, genesis, structure and functions, and the prospects for its application in teaching are presented. The solution of the problem of synthesizing the regulators in the form of the coordinate-matrix structure of the regulators is shown; the universal learning activities performed in the course of the regulators’ design are considered. The prospects for the application of visual didactic regulators are highlighted.Scientific novelty. The logic of the evolution of didactic visual aids is shown: from illustrative – through the support – to visual didactic regulators with extended didactic functions. The universal coordinate-matrix graphic realization of regulators is proved. While the amount of formal, inanimate innovations – standards, test methods of training and control, the Unified State Exam, etc., is being increased, visually presented regulators of the logical-semantic type make active impaired subject-subject interaction in educational process. Furthermore, visual didactic regulators stimulate a creative component of design and experimental activity of the teacher. It is suggested to use the concept “visual didactic regulators of the logical-semantic type” as a new unit of the terminological apparatus of Didactics. Practical significance. Practical constructions of visual didactic regulators of the logical-semantic type are proffered; possible areas of visual didactic regulators’ application in teaching technologies are revealed.